Katalog der in den Sammlungen des Deutschen Entomologischen Institutes aufbewahrten Typen - IV (Thysanoptera). - Schliephake, Gert; Gaedike, Hannelore (Contributions to Entomology = Beiträge zur Entomologie, 1970)
The fourth part of a catalogue for all the types of the Deutsches Entomologisches Institut (Eberswalde) consists Thysanoptera.